Education and HIV/AIDS : A sourcebook of HIV/AIDS prevention programs - World Bank (Washington, D.C.: World Bank, 2004)
This book aims to support efforts by countries to strengthen the role of education sector in the prevention of HIV/AIDS. It is part of the global effort to accelerate the education sector's response to HIV/AIDS.
osa, 27/09/2016
Loans
Keywords: HIV/AIDS - education; HIV/AIDS - prevention